Black and Organic Carbon Fractions in Fine Particulate Matter by Sectors in the South Hemisphere Emissions for Decision-Making on Climate Change and Health Effects - Cubillos-Montecino, F; Diaz-Robles, L (Springer, 2020)
Some databases report global emissions of certain pollutants. Emissions Database for Global Atmospheric Research (EDGAR) project is one of these, which also records emissions by sources. In this study, the emissions of black and organic carbon and fine particulate matter from the EDGAR database were used as an input to process it in the Sparse Matrix Operator Kernel Emissions (SMOKE) model. We showed the spatial distribution of the fraction of black and organic carbon in particulate matter from each source in the Southern Hemisphere. Also, we extracted these ratios for several cities in the domain of analysis. The results and methodology of this study could improve the emission inventories with bottom-up methodology in areas without information located at Southern Hemisphere. Also, it could be relevant to obtain better performance in air quality modeling at the local level for decision-making on climate change and health effects. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.